2007
DOI: 10.1111/j.1365-2125.2006.02827.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein binding of cefazolin is saturable in vivo both between and within patients

Abstract: AimsThe aims of the study were a) to determine if there is evidence of saturable protein binding of cefazolin in plasma across the range of concentrations achieved clinically (between patient variability) and b) to investigate whether saturable protein binding is also evident from trough and peak concentrations in the same patient (within patient variability). MethodsUnbound and total plasma concentrations were measured in patients who were treated with cefazolin intravenously by continuous infusion or intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…A study by Hutschala et al, administering 4 g of cefazolin 60 min prior to skin incision and an additional 2 g during closure of the incision to cardiac surgical patients, used microdialysis to determine muscle and subcutaneous tissue concentrations (14). Those authors concluded that muscle and subcutaneous tissue concentrations remained well above the MIC 90 of 1 g/ml for S. aureus, a potential wound pathogen, for at least 10 h. While free plasma concentrations were not reported, it is likely, based on total plasma concentrations and approximate cefazolin protein binding of 80 to 85%, that free-drug concentrations in plasma were similar to the tissue concentrations observed (16,17). Although the prophylaxis dosing scheme differs substantially from the standard dosing scheme for treatment administered to the patients in the current study, the overall findings of free-drug concentrations in plasma paralleling those in tissue are similar.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hutschala et al, administering 4 g of cefazolin 60 min prior to skin incision and an additional 2 g during closure of the incision to cardiac surgical patients, used microdialysis to determine muscle and subcutaneous tissue concentrations (14). Those authors concluded that muscle and subcutaneous tissue concentrations remained well above the MIC 90 of 1 g/ml for S. aureus, a potential wound pathogen, for at least 10 h. While free plasma concentrations were not reported, it is likely, based on total plasma concentrations and approximate cefazolin protein binding of 80 to 85%, that free-drug concentrations in plasma were similar to the tissue concentrations observed (16,17). Although the prophylaxis dosing scheme differs substantially from the standard dosing scheme for treatment administered to the patients in the current study, the overall findings of free-drug concentrations in plasma paralleling those in tissue are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone, cefazolin, cefonicid, and ertapenem are examples of antimicrobials for which nonlinear protein binding has been reported in the literature (4)(5)(6)(7). Binding to protein can occur in both intra-and extravascular spaces and is an important determinant of a drug's pharmacokinetics (PK), as it will impact distribution and elimination processes.…”
Section: Introductionmentioning
confidence: 99%
“…After removal of one outlier, cefazolin only achieved a C exudate :C plasma ratio of 0.51, which is at least 40% lower than the ratios achieved by all the other antibiotics tested in this study. Cefazolin as well as other antibiotics may not penetrate wounds in patients undergoing NPWT because of the high protein binding of cefazolin 21 relative to the other antibiotics observed in this study. [22][23][24][25][26] Notably, other pharmacokinetic and pharmacodynamic variables, such as elimination half-life, were in agreement with previously established values (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%